Web-geospatial water management decision support system for Tanjung Karang rice irrigation scheme, Malaysia - Mamodu, Maina Mohammed (2014)
Irrigation water management in agriculture is very important because more than 70% of fresh water resources goes to agriculture. Rice alone for instance, consumes 45% of the freshwater diverted to irrigation. Many studies have shown that water application to rice can be reduced without compromising yield; in fact, it was evident that growing rice at saturation level of moisture increase yield. Lack of correct information of the parameters for scheduling irrigation and precise measurements to determine the water balance model components are the causes of over irrigation. Hence there is a need to develop a tool that is not yet available locally to assist water managers in precision rice irrigation management. The first objective of this study was to collect field data and make in-situ field measurements on Paddy ET and crop Coefficients (Kc) for paddy using field lysimeters and field telemetry of sensors. The second objective was to develop empirical relationships between local groundwater table depths and the standing water depth in paddy fields and vadose zone saturation levels during the crop growing season. Field taken measurements on nutrients of the surface and groundwater sources were for irrigation water in the Tanjung Karang Irrigation Scheme; user-friendly and interactive Web-Geospatial decision Support System was then developed for irrigation water management in the Tanjung Karang Rice Irrigation Scheme (TKRIS) area. The system will enable farmers and irrigation managers to view, analyze and query some aspects of the farm to obtain results that are useful for decision making. The telemetry system consists of Microflex-C Sensors, remote terminal units, and data server. For the shallow groundwater measurements, three wells were established installed with a Diver sensor, to monitor water table fluctuations in the farm throughout two rice growing seasons. The nutrient contents of the irrigation water were determined by obtaining weekly water samples from the strategic points in the farm, i.e. Canals, drains, paddy field and shallow well. These samples were subjected to the standard water quality testing method to determine the quantity of the crop nutrient elements in the water such as N, P, K, NH3, and some water quality parameters such as pH, Turbidity, and Alkalinity. The web application was developed based on ESRI products. ArcGIS server 10.1, ArcGIS viewer for flex and Microsoft SQL database were used. The results from the first objective showed that the average crop coefficient (Kc) and measured rice crop evapotranspiration (ETc) of variety MR219 for the study area for the first season from February, March and April which corresponds with the early, mid and late stage of rice plant growth were 1.1, 1.3, and 1.2; 4.1, 3.9 and 4.0 mm/day respectively, with average percolation rate of 2.1 mm/day. On the other hand, the values of Kc and rice evapotranspiration for the second season from July, August and September which corresponds with early, mid and late stage of rice plant growth were 0.9, 1.0 and 1.1; 3.9, 3.7 and 4.0 mm/day respectively with an average percolation rate of 1.7 mm/day. The irrigation water from the canal which was the most important source was found to contain significant amount of N, P, and K at the rate of 25.7 kg/ha, 8.6 kg/h and 118.4 kg/ha, respectively. These information are vital to the farmers and irrigation managers; therefore, making it available online will improve decision making for best practices by the farmers. A DSS known as SWAMP (Soil Water And Management for Paddies) was developed using spatial data as input in the form of layers and published through the ArcGIS server, where the ArcGIS Viewer for flex access the data and display for viewing and analysis. The developed system is very interactive and the interface is simplified such that a novice user can explore and retrieve information. The managers can at a glance detect where to restrict and relax supply and give attention with regards to yield quantity and quality. The application of ultrasonic sensors to monitor field water depletion proved to be useful in ET monitoring and measurements to schedule irrigation. About 21% of the total water applied to the field by irrigation could be saved when contribution of groundwater is considered in the model. The newly developed SWAMP tool saves time and resources and is flexible with high accuracy in its overall output for real time information for best practice in rice precision farming. By publishing the crop water requirement and nutrients content of irrigation water, farmers will apply water strictly based on these information. Therefore reduced input leads to high efficiency and productivity for sustainable agriculture.